Rodent diversity and habitat use in a protected area of Buenos Aires province, Argentina - Isabel Elisa Gómez Villafañe; Yanina Expósito; Álvaro San Martín; Pablo Picca; María Busch (Revista Mexicana de Biodiversidad)
Habitat use of rodents is associated to environmental variables, species requirements and biological interactions. The aim of this study was to analyse the macro and microhabitat use and spatial variation in the abundance of small wild rodents that inhabit Otamendi Natural Reserve, Argentina. We studied the rodent communities in 6 habitats: riparian forest, Celtis tala forest, lowland grassland, salt marsh and 2 highland grasslands. We captured a total of 153 individual of Scapteromys aquaticus, Akodon azarae, Oxymycterus rufus, Oligoryzomys flavescens, Deltamys kempi and O. nigripes, with a trapping effort of 3636 trap-nights. The species richness is maintained by the presence of different habitats that satisfy specific requirements from specialist and generalist species, using differentially the reserve and forming communities of different specific composition in each habitat. A differential macrohabitat use was observed by all species, and a certain level of selectivity at microhabitat scale was observed in individuals of 2 species. This study shows that the diversity of environments in the Otamendi Natural Reserve, which allows the maintenance of many wild species of small rodents; confirming the high ecological and conservational value of the reserves inside an urban region.